1989
DOI: 10.1002/ijc.2910430221
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tumor and differentiation‐inducing activity of n,n‐dimethylformamide (dmf) in head‐and‐neck cancer xenografts

Abstract: The anti-tumor activity of the putative differentiation-inducing agent dimethylformamide (DMF) was assessed in 7 head-and-neck xenograft (HNX) lines transplanted into nude mice. The drug was administered intra-peritoneally at the maximum tolerated dose. A significant growth-inhibitory effect was observed in 3 out of 7 tumor lines tested. When compared with 5 conventional drugs active in patients with squamous-cell carcinoma of the head and neck (HNSCC), DMF was as effective as the most active drugs (cisplatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Although previous studies have reported the use of 14C xenograft models, , isolation and cross-sectioning of tumors after completion of the study revealed that especially large tumors were fluid filled rather than a solid mass (Figure S5 in the Supporting Information), possibly influencing tumor volume calculations based on external caliper measurements. It appears that subcutaneous implantation of 14C cells in mice results in the growth of cystic tumors (Prof. Dr. R. Brakenhoff, VU University Medical Center, Amsterdam, The Netherlands, personal communication).…”
Section: Resultsmentioning
confidence: 95%
“…Although previous studies have reported the use of 14C xenograft models, , isolation and cross-sectioning of tumors after completion of the study revealed that especially large tumors were fluid filled rather than a solid mass (Figure S5 in the Supporting Information), possibly influencing tumor volume calculations based on external caliper measurements. It appears that subcutaneous implantation of 14C cells in mice results in the growth of cystic tumors (Prof. Dr. R. Brakenhoff, VU University Medical Center, Amsterdam, The Netherlands, personal communication).…”
Section: Resultsmentioning
confidence: 95%
“… 4 , 5 DMF reduces the cholesterol level and increases the concentration of bile acid, indicating that there is a relationship between DMF and gut microbiotas. 6 Previous studies have also shown that DMF can promote apoptosis and inhibit tumor growth, such as head and neck cancer, 7 prostate cancer, 8 and ovarian cancer. 9 On the other hand, DMF enhances hepatocarcinogenicity in animal model.…”
Section: Introductionmentioning
confidence: 99%
“…2), a widely used polar solvent, exhibits synergistic killing of HL‐60 human promyelocytic leukemia cells when combined with ultrasound 11. Anti‐tumor properties of DMF in the absence of ultrasound have been reported, 27 but its potential use for cancer therapy was limited due to the hepatotoxic effect of DMF. Jeffers et al demonstrated the cell killing by DMF and ultrasound at DMF concentrations (0.11 M), which by themselves were non‐toxic, thus improving the prospects for therapeutic application of DMF for locally intense chemotherapy 11.…”
Section: Resultsmentioning
confidence: 99%